2010
DOI: 10.1128/mcb.01373-09
|View full text |Cite|
|
Sign up to set email alerts
|

Tandem Phosphorylation of Serines 221 and 318 by Protein Kinase Cδ Coordinates mRNA Binding and Nucleocytoplasmic Shuttling of HuR

Abstract: Stabilization of mRNA by the ubiquitous RNA binding protein human antigen R (HuR), a member of the embryonic lethal abnormal vision (ELAV) protein family, requires canonical binding to AU-rich element (ARE)-bearing target mRNA and export of nuclear HuR-mRNA complexes to the cytoplasm. In human mesangial cells (HMC) both processes are induced by angiotensin II (AngII) via protein kinase Cδ (PKCδ)-triggered serine phosphorylation of HuR. By testing different point-mutated Flag-tagged HuR proteins, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 64 publications
(91 reference statements)
6
121
0
1
Order By: Relevance
“…On the other hand, PKC has been implicated in the stabilization of a variety of other mRNAs such as, p21, GAP-43 and IL-1β itself [19,20,22,23]. Importantly, PKC has been convincingly implicated in COX-2 mRNA stabilization in several recent studies [21,31,44,54,68] and, indirectly, in IL-6 mRNA stabilization in one older study [69]. In astrocytes, PKC was previously shown to be important for IL-6 induction after IL-1β [70].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PKC has been implicated in the stabilization of a variety of other mRNAs such as, p21, GAP-43 and IL-1β itself [19,20,22,23]. Importantly, PKC has been convincingly implicated in COX-2 mRNA stabilization in several recent studies [21,31,44,54,68] and, indirectly, in IL-6 mRNA stabilization in one older study [69]. In astrocytes, PKC was previously shown to be important for IL-6 induction after IL-1β [70].…”
Section: Discussionmentioning
confidence: 99%
“…The most studied modification of the HuR proteins is phosphorylation. It has been demonstrated that phosphorylation at specific serines or a threonine of HuR can lead to altered cellular localization of the protein and, in one case, can increase the RNA-binding affinity of HuR (Doller et al 2010;Srikantan and Gorospe 2012). One report indicated that heat shock induces ubiquitination of HuR at Lys 182, leading to degradation of HuR and decreased levels of HuR target mRNA abundance (Abdelmohsen et al 2009).…”
mentioning
confidence: 99%
“…Upon HuR phosphorylation, different cellular responses have been described (Abdelmohsen, 2007 a,b;Doller et al 2008;Kim 2008a-c). Whereas the HuR capability for binding to RNA targets increases or decreases when Chk2 phosphorylates HuR at Ser88 or Ser100 residues, respectively (Abdelmohsen et al 2007b), the addition of a phosphate group to Ser158, Ser221 and Ser318 by PKC favors the cytoplasmic localization of HuR instead of the preferred nuclear localization of the protein (Doller et al 2008(Doller et al , 2009, along with an enhancement in the mRNA binding (Doller et al 2007). …”
mentioning
confidence: 99%